A construção do empoderamento de usuários e familiares nas práticas de um centro de atenção psicossocial - Pedroso, Carlos Eduardo [UNIFESP] (2016)
The Brazilian Psychiatric Reform is a process of reorientation and restructuring of mental health care in the country that involves the creation of new substitutive psychosocial services to the hospital-centered model and in the alignment of those to the conceptual perspective of deinstitutionalization, namely, the deconstruction of madness in the social field as alienation, disability and dangerousness locus where it?s social, scientific, political and culturally recognized. For this, these mental health treatment centers, particularly the psychosocial care centers, are intended to develop practices for the construction of the mentally ills citizenship, through the involvement of users and relatives and the promotion of their autonomy, value and social power. Therefore, it is important to understand, in the current national mental health care public policy, the process of empowerment of users and their families, understood as the increased autonomy and personal and collective power of individuals and groups subject to social oppression. Thus, we produced a participatory qualitative research, which was intended to investigate the construction of the empowerment of users and family members in the practices undertaken by the mental health treatment center from Itanhaém, São Paulo. For this, we conducted historical-documentary survey, participant observation, focus groups with users and families, and production of narratives by the groups in the institution. The research interlocutors participated in the interpretive process of the narratives and the collective experiences in last groups meetings, which enabled the critical and reflective deepening of participants. The information production analysis was built from the dialectical hermeneutics perspective and it was undertaken in four interpretive steps: personal empowerment; group empowerment; community empowerment; and care processes. We concluded that the empowerment process is different among subjects. For participant users, it is produced in the personal appreciation, the development of some self-help strategies, the production of initial networks of mutual help and support, and the creation of joint community actions with professionals. For family interlocutors, empowerment develops only in some practices of the service where they increase their self-esteem, resignify the family member sickening process and create their own care means. The practices of the service studied, also understood as care, provide empowerment of individuals through listening, reception care and group and community strategies that produce horizontal political relations and shared experience and knowledge between professionals and users/family. Contradictorily, the care developed also hinders the process of empowerment of individuals by focusing on drug treatment, hierarchy power relations between the actors, the heteromanagement of decisions and care and, consequently, political centrality in technical and medical professionals. We understand that the tension in care processes corresponds to the contradiction between the different models of care, the hegemonic psychiatric paradigm and the psychosocial care model, which act concurrently in the relationship between professionals and users/family. The empowerment process requires the involvement of all actors, in order to break the oppressive relations to the real increase in autonomy and power of these.